Genetic Variation in Cytochrome b-Hinf1 and -Alu1 Gene Correlated to Body Size in Soang Gourami (Osphronemus goramy) from Single Spawning - Agus Nuryanto; Nael Huda Qonita; Hendro Pramono; Kusbiyanto Kusbiyanto; Petrus Hary Tjahja Soedibja (Biosaintifika: Journal of Biology & Biology Education)
Soang gourami fingerling shows variable body sizes eventhough resulted from single spawning. Differences in body sizes among individuals is assumed to be correlated to their genetic component which can be studied using cytochrome b gene PCR-RFLP marker. This study aimed to determine specific PCR-RFLP marker among different sizes of soang gourami collected from single spawning. Genomic DNA was isolated using Chelex method. Cytochrome b gene were amplified and digested using four restriction enzymes. Specific markers were analyzed descriptivelly based on DNA band pattern appear in agarose gel. The result showed that PCR-RFLP markers of Cytochrome b-HinfI of 315 bp, and 210 bp, and also Cytochrome b-AluI of 334 bp and 189 bp are specific markers for large individuals, whereas small individuals are characterized by having Cytochrome b- HinfI 366 bp, and 159 bp and Cytochrome b-AluI 525 bp fragments. It is observed that genetic variation of Cytochrome b-HinfI and -AluI markers are possitively correlated to body size in soang gourami fingerling. Therefore, both cytochrome b-HinfI and -AluI gene can be reffered as specific markers to differentiate among different sizes of soang gourami strain fingerling from single spawning. This result proved that genetic divergences among individuals can be related with certain quantitative characters, such size related. Therefore our study can contribute on fisheries development, especially by providing new technique for fingerling selection to obtain high quality fingerling and also provide new insight the application of molecular technique in fisheries.